Práticas de Leitura: uma discussão a partir de falas de professores da educação básica do município de Breves - RODRIGUES, Mateus dos Santos (2024)
This work aims to analyze and highlight the importance of reading in the teaching-learning process of basic education students, as well as its practice in schools in Breves, on the island of Marajó. The research construction has a theoretical foundation in bibliographies that highlight aspects related to the cognitive and emotional development of students provided by reading, skills such as, for example, interpretation and production of texts, vocabulary extension, among other various benefits. To carry out the research, interviews were carried out with four basic education teachers in Breves, to analyze and understand their conceptions of working with reading. The research result showed that teachers have a remarkable conception of working with reading in the classroom, understanding it as one of the determining factors for the teaching and learning process, as the skills provided by reading practice are essential for improving the intellectual capabilities of basic education students.